New CMOS Realization of Z Copy Voltage Differencing Buffered Amplifier and Its Current-Mode Filter Application - Guney, Arda; Alaybeyoglu, Ersin; Kuntman, Hakan (IEEE, 2013)
In this paper, a new CMOS realization of Z Copy Voltage Differencing Buffered Amplifier (ZC-VDBA) is presented. The performance of the proposed circuit is demonstrated on a new current-mode Kerwin-Huelsman-Newcomb (KHN) filter application, employing two ZC-VDBAs and two grounded capacitors. The circuit simulations are verified using BSI M3 0.18 mu m level-7 SPICE parameters.
Keywords: CMOS integrated circuit; Z copy voltage differencing bufferred amplifier; KHN filter; Current mode; Engineering; Science & Technology - Other Topics